(untitled) (Third Sector Social Economic Review, 2022)
Plastic production, which has increased approximately ten times in the world since 1950, poses a serious threat to the environment and human life due to its widespread usage. For this reason, projects are being developed and legal regulations are being introduced in Turkey, as in the rest of the world, for the recycling and reuse of plastic waste instead of releasing it into the environment. Despite the many steps taken under the umbrella of sustainability with plastic wastes, it was seen that the concepts of ""sustainable entrepreneurship"" and ""sustainable business model"" were not examined between 1960-2022 within the scope of the TR Index. This study aims to examine the sustainable entrepreneurship activities of plastic recycling enterprises in Adana, which are frequently featured in both national and international press due to the release of plastic wastes into the environment, through a sustainable business model. In line with the purpose of the study, face-to-face interviews were conducted with the owners/partners of five plastic recycling businesses in Adana within the framework of the sustainable business model developed by Stubbs and Cocklin (2008). As a result of the research, in parallel with the literature, it was determined that environmental factors beyond the control of the business owner/partner came to the fore in the sustainable entrepreneurship process. It was seen that the participants focused on protecting the environment by using waste plastic as raw materials and/or converting it into different products, contributing to employment and the local economy, and at the same time prioritizing profitability. It was determined that lobbying activities were also implemented as part of the sustainable business model.